Fizz : harness the power of word of mouth marketing to drive brand growth - Wright, Ted, 1967- (McGraw-Hill Education, 2015)
-- -- -- -- -- FizzFizz -- Fizz"Ted's actionable truths ('for influencers, sharing stories is an expression of love') make this excellent book the guidebook for brand professionals interested in word of mouth marketing. Buy it today, and start growing your business faster tomorrow.""Ted Wright is the foremost thought leader on word of mouth marketing, and Fizz"The best and most practical book about word of mouth marketing, ever. Fizz